Effect of cattle manure on the performances of maize (Zea mays L) grown in forest-savannah transition zone Southwest Nigeria - Eleduma AF; Aderibigbe ATB; Obabire SO (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
The contribution of inorganic fertilizer to enhance crop growth and yield cannot be ignored, but on the other hand their indiscriminate use is causing deterioration of the soil structure and soil acidity. A field experiment was conduct at the Teaching and Research Farm, Rufus Giwa Polytechnic, Owo, Ondo state, Nigeria to study the effect of variable rate of cattle manure on the growth and yield of maize (Zea Mays L). Five rates of cattle manure: control, 5, 10, 15, and 20 t/ha-1 replicates three times laid out in a Randomized Complete Block Design (RCBD) was evaluated. Data were collected on vegetative traits and yield component and statistically analyzed. The growth and yield attributes increased significantly accordingly to the rates of cattle manure due to continuous supply of nutrient. The control plot gives significantly lower means and maize that received 20 t ha-1 recorded the highest mean in all growth and yield parameter evaluated in the study. Applications of 20 t ha-1 cattle manure significantly improve vegetative growth and yield attributes of maize plant and therefore recommended for adoption by resource-poor farmer can adopt the use of cattle manure at 20 t ha-1 as substitute for inorganic fertilizer, thus reduce environmental pollution posed by the disposal of the cattle waste and ultimately improve yield in the study area.